Regulatory development and public policy against child sexual abuse in Colombia - Ibarra Padilla, Adelaida María; Lora Ramírez, Ricardo Omar; Preciado Gómez, Yolanda Cecilia; Ibarra Padilla, Adelaida María; Lora Ramírez, Ricardo Omar; Preciado Gómez, Yolanda Cecilia; Ibarra Padilla, Adelaida María; Lora Ramírez, Ricardo Omar; Preciado Gómez, Yolanda Cecilia (Corporación Universitaria Americana, 2020)
Sexual abuse against children and adolescents is a form of serious abuse that violates sexual freedom and human dignity and can cause physical and psychological harm to the victim. This article analyzes the regulatory development of the subject in Colombia and the public policy measures implemented in the country for its prevention and remedy. To achieve this goal, the instruments of Public International Law on these issues inserted in domestic law were studied. Likewise, the measures that are being implemented by the competent authorities such as the National Police and the Colombian Institute of Family Welfare (ICBF) are analyzed, as well as the work that educational establishments do on the subject. It is concluded that this problem requires an interdisciplinary and multidimensional approach. The study shows that the measures in force on the matter are mostly of a sanctioning and reparative nature, but few of a preventive nature. The prevention of this scourge requires mental health measures, sexual education, psychosocial support to families in extreme poverty and the articulated work between families, schools and the competent authorities.